General practitioner trainees' in-consultation generation of clinical questions for later answering: prevalence and associations. (24th March 2017) - Magin, Parker; Tapley, Amanda; Davey, Andrew; Morgan, Simon; Holliday, Elizabeth; Ball, Jean; Wearne, Susan; Henderson, Kim; Catzikiris, Nigel; Mulquiney, Katie; Spike, Neil; Kerr, Rohan; et al.
Abstract: Background: As well as generating patient-specific questions, patient consultations are a rich source of questions relating to clinicians' need to acquire or maintain wider clinical knowledge. This is especially so for GP trainees. Objectives: To establish the prevalence and associations of GP trainees' generation of 'learning goals' (LGs: questions generated during clinical consultations for intended post-consultation answering). Also, to characterize the type of learning goals generated. Methods: A cross-sectional analysis (2010–15) of an ongoing cohort study of Australian GP trainees' consultations. Once each 6-month training term, trainees record detailed data of 60 consecutive consultations. The primary outcome was generation of an LG. Analysis was at the level of individual problem/diagnosis managed. The secondary outcome was the problems/diagnoses to which the LGs related. Results: One thousand one hundred and twenty-four trainees contributed data for 154746 consultations including 222307 problems/diagnoses. LGs were generated for 16.6% [95% confidence intervals (CI) = 16.4–16.7] of problems/diagnoses, in 22.1% (95% CI = 21.9–22.3%) of consultations. Associations of LGs included patient factors: younger age and having seen the trainee previously; trainee factors: earlier training stage, being overseas-trained and the trainee's training organization; consultation factors: longer duration, addressing a chronic disease, referring the patient, organizing follow-up, organizing investigations and accessing in-consultation information. LGs were commonly generated for skin (12.9% of all learning goals), musculoskeletal (12.7%) and respiratory (8.7%) problems. LGs were generated for 31.8% of male genital, 27.0% of neurological and 23.3% of eye problems. Conclusion: Australian GP trainees frequently generate questions in-consultation to be pursued post-consultation. Prevalence, 'complexity' and familiarity of clinical topic area influenced LG generation.